Developing graphical visualization for understanding the pattern of students performance in exam / Anisah Rosli and Norfiza Ibrahim - Rosli, Anisah; Ibrahim, Norfiza (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Education is a necessary human virtue, a foundation for a good life, and a symbol of liberty. This project was made to analyses the data requirement, dataset of student performance during examination also to design a students’ performance dashboard that guides students to know which courses to focus more and which courses are linked together for their exams and last but not least to evaluate the functionality of the dashboard using User Acceptance Testing. The aim is to visualize the importance of understanding students’ performance during exams using a dashboard and evaluate its functionality. The Design Science Research methodology (DSRM) was used throughout the development process of this project. Moreover, the data cleaning and transform were made fully with Microsoft Excel. The data visualization was made using Microsoft Power Bi. The evaluation of the project was made using User Acceptance Test (UAT) with the results of 49% of respondent agree and other 50% strongly agree intend on using KPPIM UiTM Perlis Student Performance Dashboard as guidance tool.